2006
DOI: 10.1002/marc.200600123
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Shrinking Networked Materials from the Cross‐Linking Copolymerization of Spiroorthocarbonate with Bifunctional Oxetane

Abstract: Summary: The cationic ring‐opening copolymerization behavior of SOC1 with BOXT and the properties of the obtained cross‐linked copolymers are described. SOC1 and BOXT are cationically copolymerized under various feed ratios to obtain the corresponding cross‐linked copolymers in 73–96% yields. The volume change during copolymerization could be controlled by the addition of SOC1 to obtain non‐shrinking or volume‐expanding copolymers. The glass transition temperatures (Tg) of the copolymers also decrease linearly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…A similar mechanism was proposed for the thermal cross-linking of TOSU with another bifunctional oxatane monomer BOXT [125]. The results reveal that these monomers were polymerized in a sequential manner, that is, first TOSU is polymerized and propagating ends initiates the polymerization of BADGE (Scheme 11.37).…”
Section: Expandable Monomersmentioning
confidence: 52%
See 3 more Smart Citations
“…A similar mechanism was proposed for the thermal cross-linking of TOSU with another bifunctional oxatane monomer BOXT [125]. The results reveal that these monomers were polymerized in a sequential manner, that is, first TOSU is polymerized and propagating ends initiates the polymerization of BADGE (Scheme 11.37).…”
Section: Expandable Monomersmentioning
confidence: 52%
“…Several attempts have been made to design systems that undergo little or no volume changes upon polymerization since many important technologies, including dental materials, composites without strain stress, stereolithography, and many imaging applications do not tolerate volume shrinkage during polymerization [123][124][125][126].…”
Section: Expandable Monomersmentioning
confidence: 99%
See 2 more Smart Citations
“…Bailey and collaborators pioneered the studies on the usage of SOCs as expanding monomers [4][5][6]. Since then, numerous reports on the synthesis of new SOCs have appeared [7][8][9][10][11], and employed as shrinkage reduction additives in dioxirane polymerization by using boron trifluoride as catalyst and elevated temperature [12] as well as in cationic photopolymerization of an aromatic dioxirane [13]. Also, previous studies from our group have demonstrated the effectiveness of epoxy and oxetane functionalized SOC [14,15] as low shrinkable agents in cationic UV curing of epoxy and oxetane photocurable formulations.…”
Section: Introductionmentioning
confidence: 99%